2015
DOI: 10.4028/www.scientific.net/amm.761.566
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Lean Behavior in Business Development and IT Department

Abstract: Lean behavior is an essential element to create a culture of continuous improvement culture in a service organization. Continuous improvement is defined as the never-ending efforts for improvement involving everyone in an organization. The purpose of this study is to evaluate the changes of behavioral practices after the introduction of lean tools and discuss the effects of lean behavior in developing a culture of continuous improvement in an office environment. This study adopted a self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Abdallah et al (2021) stated that both social (human aspects) and technical (tools and techniques) LM were discovered to have a beneficial impact on operational performance in manufacturing SMEs. Puvanasvaran et al (2015) performed a study of lean behavior in business development and information technology (IT) found out that the employees were lack of substantial lean implementation expertise and skillsets. The results revealed that employees' lean behaviour practices had been improved after adopting the lean tools.…”
Section: Development Of Lm Maturity Conceptual Modelmentioning
confidence: 99%
“…Abdallah et al (2021) stated that both social (human aspects) and technical (tools and techniques) LM were discovered to have a beneficial impact on operational performance in manufacturing SMEs. Puvanasvaran et al (2015) performed a study of lean behavior in business development and information technology (IT) found out that the employees were lack of substantial lean implementation expertise and skillsets. The results revealed that employees' lean behaviour practices had been improved after adopting the lean tools.…”
Section: Development Of Lm Maturity Conceptual Modelmentioning
confidence: 99%